SPE Annual Technical Conference and Exhibition 2019
DOI: 10.2118/196017-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Inter-Fracture Injection and Production in a Cluster Well to Enhance Oil Recovery

Abstract: Applications of cluster wells and hydraulic fracturing enable commercial productivity from unconventional reservoirs. However, well productivity decrease rapidly for this type of reservoirs, and in many cases, it is difficult to maintain a productivity that is economical. Enhanced oil recovery (EOR) is therefore needed to improve well performance. Traditional fluid injection from other wells are not feasible due to the ultra-low permeability, and fluid Huff-n-Puff also fails to meet the expected recovery. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The overall recovery observed for hydrocarbon gas (8.74%) was very similar to that for CO 2 (8.26%), and the difference was attributed to differences in the compressibility, viscosity, and phase behavior of the injected fluids. This observation was supported by Hoffman (2012), who reported that the injections of hydrocarbon gas and CO 2 were similarly effective as EOR methods. Du and Nojabaei (2019) reviewed the state of the gas-injection-based EOR in shale reservoirs, covering the spectrum of available information on the subject at the time.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…The overall recovery observed for hydrocarbon gas (8.74%) was very similar to that for CO 2 (8.26%), and the difference was attributed to differences in the compressibility, viscosity, and phase behavior of the injected fluids. This observation was supported by Hoffman (2012), who reported that the injections of hydrocarbon gas and CO 2 were similarly effective as EOR methods. Du and Nojabaei (2019) reviewed the state of the gas-injection-based EOR in shale reservoirs, covering the spectrum of available information on the subject at the time.…”
Section: Introductionmentioning
confidence: 56%
“…Using very coarse 2D areal grids, Zhu et al (2017) investigated by means of numerical simulation the performance of the interfracture injection and production system proposed by Dombrowski et al (2015) and reported significant incremental recoveries of oil after 5,000 days of CO 2 injection into shale reservoirs of various permeabilities and conducted an extensive sensitivity analysis. The authors proposed hydrocarbon gas as an alternative to CO 2 because of its lower cost, easy availability, lower viscosity (expected to lead to a higher injectivity and a faster oil recovery), and similar oil recovery performance-in agreement with the observations of Hoffman (2012) and Gala and Sharma (2018). He et al (2019) used a compartmental embedded discrete fracture model to study numerically the application of the interfracture injection and production approach in a cluster well using CO 2 as the injection gas.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Enhancing oil recovery (EOR) is crucial for oilfields to obtain stable oil production. Water flooding is a dominating enhanced oil recovery technique owing to its low cost, easy operation, and less pollution [1][2][3][4]. Therefore, it is significant for EOR to study the transport mechanisms of multiphase flow and distribution characteristics of fluids.…”
Section: Introductionmentioning
confidence: 99%